Implementation Employee Wellbeing: Analysis of Work-Life Balance, Resilience, Assessment, and Coaching - Agustian Zen; Zahara Tussoleha Rony (PT FORMOSA CENDEKIA GLOBAL, 2023)
This scientific article is to provide an overview of existing scientific articles from the point of perception of researchers. The method used as this reflection uses a graphic writing style; analysts gather the necessary data from additional sources before analyzing and refining it properly, Information for research is collected using additional data collection methods, additional details are collected from books, articles, research papers, lecture notes, and the Internet. A selection of related scientific articles are selected, investigated, and revised during the literature review. The variables explained with the results and discussion meet the answerability in accordance with the purpose of this scientific article, which is to describe by providing perspective, and this variable is followed by other variables that can be used as differentiators, as well as the object of research, as well as the model of the results of the study.